Correlation between the values of circulating blood elements with the size of spleen in the presence of schistosomal splenomegaly - Vasconcellos,Leonardo de Souza (2018)
Abstract Purpose: To evaluate a possible relationship between the size of the spleen and values of circulating blood elements in patients with schistosomatic splenomegaly. Methods: ixty one patients with hepatosplenic schistosomiasis mansoni underwent a clinical exam and peripheral venous blood was collected for a hemogram. The erythrocyte, hemoglobin, hematocrit, leukocyte, and platelet values were determined. All patients underwent abdominal ultrasound to measure the spleen. The hematological test results were compared to the size of the spleen. Results: The size of the spleen varied from 14.0 to 28.4 (19.9 ± 3.7) cm according to the ultrasound image. Thrombocytopenia was observed 58 (95%) patients, leukopenia in 55 (90%) patients, and anemia in 32 (52.4%) patients. Leukopenia was proportional to splenomegaly. Conclusion: Schistosomal splenomegaly leads to leukopenia in direct proportion to the size of the spleen.